Living in Cold Blood: Arcobacter, Campylobacter, and Helicobacter in Reptiles - Gilbert, Maarten J.; Duim, Birgitta; Zomer, Aldert L.; Wagenaar, Jaap A. (Frontiers in Microbiology, 2019)
Species of the Epsilonproteobacteria genera Arcobacter, Campylobacter, and Helicobacter are commonly associated with vertebrate hosts and some are considered significant pathogens. Vertebrate-associated Epsilonproteobacteria are often considered to be largely confined to endothermic mammals and birds. Recent studies have shown that ectothermic reptiles display a distinct and largely unique Epsilonproteobacteria community, including taxa which can cause disease in humans. Several Arcobacter taxa are widespread amongst reptiles and often show a broad host range. Reptiles carry a large diversity of unique and novel Helicobacter taxa, which apparently evolved in an ectothermic host. Some species, such as Campylobacter fetus, display a distinct intraspecies host dichotomy, with genetically divergent lineages occurring either in mammals or reptiles. These taxa can provide valuable insights in host adaptation and co-evolution between symbiont and host. Here we present an overview of the biodiversity, ecology, epidemiology, and evolution of reptile-associated Epsilonproteobacteria from a broader vertebrate host perspective.